Event as the central construal of psychological time in humans - Stojić, Sandra; Nadasdy, Zoltan (Frontiers in Psychology, 2024)
Time is a fundamental dimension of our perception and mental construction of reality. It enables resolving changes in our environment without a direct sensory representation of elapsed time. Therefore, the concept of time is inferential by nature, but the units of subjective time that provide meaningful segmentation of the influx of sensory input remain to be determined. In this review, we posit that events are the construal instances of time perception as they provide a reproducible and consistent segmentation of the content. In that light, we discuss the implications of this proposal by looking at "events" and their role in subjective time experience from cultural anthropological and ontogenetic perspectives, as well as their relevance for episodic memory. Furthermore, we discuss the significance of "events" for the two critical aspects of subjective time -duration and order.Because segmentation involves parsing event streams according to causal sequences, we also consider the role of causality in developing the concept of directionality of mental timelines. We offer a fresh perspective on representing past and future events before age 5 by an egocentric bi-directional timeline model before acquiring the allocentric concept of absolute time. Finally, we illustrate how the relationship between events and durations can resolve contradictory experimental results.Although "time" warrants a comprehensive interdisciplinary approach, we focus this review on "time perception", the experience of time, without attempting to provide a comprehensive overview of the rich philosophical, physical, psychological, cognitive, linguistic, and neurophysiological context.